Yarrowia lipolytica as an Oleaginous Cell Factory Platform for Production of Fatty Acid-Based Biofuel and Bioproducts - Abghari, Ali; Chen, Shulin (Frontiers in Energy Research, 2014)
Today’s biotechnologists seek new biocatalysts to meet the growing demand for the bioproducts. This review critically evaluates the potential use of Y. lipolytica as an oleaginous cell factory platform. This yeast has undergone extensive modifications for converting a wide range of hydrophobic and hydrophilic biomass, including alkane, oil, glycerol and sugars to fatty acid-based products. This article highlights challenges in the development of this platform and provides an overview of strategies to enhance its potential in the sustainable production of biodiesel, functional dietary lipid compounds and other value-added oleochemical compounds. Future applications of the recombinant Y. lipolytica platform are also discussed.